Economic growth and income inequality - Vallejo, Luis Eudoro (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Economic growth, besides being a very important goal of economic policy is conceived, by some theorists, such as economic development. However, as suggested by Amartya Sen, growth is a means to development, as it has to do with the welfare of the people and therefore should incorporate not only economic variables, but also social, cultural , political and environmental, among others. In other words, economic development is multidimensional.